Corrigendum (Management Communication Quarterly, 2015)
Christensen, L. T., Morsing, M., & Thyssen, O. (2014). Discursive Closure and Discursive Openings in Sustainability. Management Communication Quarterly, 29 (1), 135–144. Original DOI: 10.1177/0893318914563574 A footnote is added, p. 135: 1 The term ”license to critique” was initially suggested in Knudsen, H. (2004). Licens til kritik – og andre måder at bruge værdier på i organisationer. In: Pedersen D (Ed.) Offentlig ledelse i managementstaten. København: Samfundslitteratur: 159-175.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wODkzMzE4OTE1NTczODI4